The extent and causes of dropouts of Mohammedan pupils in Zamboanga City - Medina, Ricardo C. 1919- (s.n.], 1961)
In order to determine the veracity of the allegation that human erosion occurs in greater proportion among minority groups of the population, particularly among the Muslim groups, this present investigator decided to look into the extent and causes of dropouts among Muslim pupils in two mixed schools and two purely Muslim schools in Zamboanga City Schools Division. It is hoped that the results of this study will give a faithful picture of the situation and at the same time will induce further studies in other localities.